Influences of the watchdog role of broadcast media in Nigeria - Gainaka, Abdu Maryam (2020)
The watchdog role of the media is a fundamental responsibility of the media especially in a democracy. In Nigeria, the constitution and some enabling laws like the Freedom of Information Act (FOIA) have given the media the duty and responsibility to “uphold the responsibility and accountability of the government to the people” and some legal backing to have more access to information of public importance from government and public institutions. However, media watchdogging is often identified with the press (print media) in Nigeria from colonial era to the present democratic dispensation. Guided by the social responsibility theory of the media, this study was therefore, an investigation of how broadcast media in Nigeria interpret the watchdog role as well as an exploration of the factors that influence how they perform the role and ways that can improve their performance of the role. The study was conducted using the qualitative case study research method. Data was collected using semi structured in depth interview and it was analyzed using the thematic analysis. The informants for the study comprised of senior editors and field reporters which were were sampled purposively from FRCN, a government owned radio station and AIT, a privately owned television station. Findings of the study revealed that broadcast media in Nigeria understand the watchdog role as a social responsibility like it is conceptualized in literature and they perform the role through investigative reporting and through broadcast programmes. The study also found that owners influence, broadcast news commercialization, self-censorship and the general laxity of broadcast media practitioners to explore the FOIA influence the watchdog role performance of broadcast media. The study concludes that broadcast media in Nigeria need to engage more in investigative journalism like there print counterpart and more regulation is required to curb owners influence. Broadcast media practitioners should also explore the FOIA to enhance their watchdog role.